Addiction and Choice: Theory and New Data - Heyman, Gene M. (Frontiers in Psychiatry, 2013)
Addiction’s biological basis has been the focus of much research. The findings have persuaded experts and the public that drug use in addicts is compulsive. But the word “compulsive” identifies patterns of behavior. Thus, the question is not whether addiction has a biology, but whether it is sensible to say that addicts use drugs compulsively. Research shows most of those who meet the American Psychiatric Association’s criteria for addiction quit using illegal drugs by age thirty, that they usually quit without professional help, and that the correlates of quitting include legal concerns, economic pressures, and the desire for respect, particularly from family members. That is, the correlates of quitting are the correlates of choice. However, addiction is, by definition, a disorder, and thereby not beneficial in the long run. This is precisely the pattern of choices predicted by quantitative choice principles, such as the matching law, melioration, and hyperbolic discounting. Although the brain disease model of addiction is perceived by many as received knowledge it is not supported by research or logic. In contrast, well established, quantitative choice principles predict both the possibility and the details of addiction.